The maiden heist [videorecording (DVD)] - Hewitt, Peter, 1962-; Harden, Marcia Gay; Freeman, Morgan; Macy, William H., 1950-; Walken, Christopher, 1943- (Sony Pictures Home Entertainment, 2009)
Charles, Roger, and George are museum security guards who take their jobs very seriously. But when they learn their favorite artworks are being sent to another museum, they concoct a plan to switch the real masterpieces with fakes. All goes well until a mistake forces these first-time thieves into a last-minute escapade.